Nanostructure Semiconductor Optical Amplifiers Building Blocks for All-Optical Processing - Rostami, Ali.; Baghban, Hamed; Maram, Reza.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
"Nanostructure Semiconductor Optical Amplifiers" reviews all-optical processing methods currently available and presents semiconductor optical amplifiers (SOAs) as a new building block for this purpose. The authors discuss the overcomes of high frequency operation of SOAs and propose a new all-optical pumping method for the implementation of semiconductor optical amplifiers.
Quantum-Dot Semiconductor Optical Amplifiers, Basic Principles, Design Methods, and Optical Characterizations -- Simulation Methods of QD-SOAs -- Techniques toward High Speed Operation of SOAs -- Applications and Functionalities -- Applications of SOA-based Circuits in All-Optical Signal Processing and Switching.
Keywords: Optical materials; Electronic materials; Microwaves; Optical engineering; Semiconductors; Optics; Electrodynamics; Optical and Electronic Materials; Microwaves, RF and Optical Engineering; Semiconductors; Classical Electrodynamics